Challenges of Information Technology Education Student’s Online Classes during the Covid-19 Pandemic in Selected Public Colleges and Universities in the Philippines - Balahadia, Francis F. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose- Many educational systems across the world have shifted to online learning methodology as a measure against Covid-19 Pandemic to continue educating students. This phenomenon is causing a lot of complications to the educational system around the world in the context of developing countries, especially to the public state colleges and universities. This paper aims to identify and describe the challenges of online learning from the perspective of Information Technology Education (ITE) students in the public state colleges and universities during the COVID-19 pandemic. Method- It used descriptive research for the conducted of the study wherein survey questionnaires were sent out via electronic survey in different state colleges and universities in the Philippines. The evaluations were calculated using descriptive statistics and Chi-square and responses were compared between their profiles using a nonparametric test. Results- The findings obtained the demographic profile of the ITE students with the degree of BS Information Technology, BS Computer Science, and BS Information System such courses, year level, and place they live. Additionally, the study gained a significant relationship between student profile in the device used in class, internet connectivity, student type of data connection, capability to attend online class, and their commitment to participate and submit class requirements. The study identifies different interrelated challenges such as the majority of the student only using smartphones in online learning and poor internet connection as they tried to adapt to online learning because they are committed to participating and submitting requirements. Conclusion- The study gives insights into the current condition experienced by the students in the school administrations and officials, and faculty as well to strengthen the appropriate online teaching mode and other practices applicable to the students. It can also use to emphasize to be more responsive to the learning needs of the IT students, especially beyond the conventional classrooms. Recommendations- It is suggested that educational institutions must create appropriate and effective content, and provide digital literacy training to current faculty to improve learning outcomes. Lastly, a strong Information Communication Technology Office that focuses on the development of a different website and mobile application that assist the need of the students and faculty may be established.